Salts and Their Distribution in the McMurdo Region, Antarctica - Keys, John Ross (11663632) (1980)
Salts are widespread in the cold, arid McMurdo region of Antarctica. They exist in a variety of deposit types from massive subglacial and sub-lake deposits containing up to 1010 kilograms of salt, down to traces in soil, snow and ice. However, deposits on rock and soil typically amount to a few grams of salt. At least 30 salt phases are known but only 10 of these are widespread. These 10 are thenardite, gypsum, halite, calcite, darapskite, soda nitre, mirabilite, bloedite, epsomite and hexahydrite. The distribution of salts has been examined on two scales, local and regional. The local scale extends from individual deposits to areas of a few square kilometres. The regional scale covers McMurdo oasis, McMurdo Sound and Ross Island, though areas in McMurdo oasis, and particularly Taylor Valley receive most attention. Local distribution is controlled by salt migration and separation. Migration is induced by water and wind, with soil brines moving as thin liquid films, by capillarity and under the influence of gravity. Deflation and asymmetric salt accumulation provide evidence that wind is important. Separation of phases is a consequence of different physico-chemical properties of salts, and environmental conditions, including site aspect, ambient temperature and humidity. Eutectic temperature is a fundamental salt property but solubility is also important. Several salt deposits containing separated (fractionated) phases have been found in the region. Separation is achieved mainly by fractional dissolution and crystallization and the most evolved product of the general separation sequence is calcium chloride. The separation processes, together with salt migration, obscure the sources of the salts. Regional distribution of salts has been characterized by determining the relative frequency at which specific phases are encountered at increasing distance from the coast and above sea level. Chloride and sodium phases decrease, whereas magnesium phases increase in frequency away from the coast. Sulphates-to-chloride and nitrates-to-chloride ratios increase with increasing distance. Calcium and carbonate show little change except in Taylor Valley where a marked decrease is apparent. This regional distribution is mainly dependent on the sources of the salts. The marine source is most important, contributing almost all of the chloride, sodium, sulphate and probably nitrate ions that are present. Chemical weathering is the predominant source of magnesium, calcium and carbonate ions probably via reactions of mafic, ferromagnesian minerals in local rocks and regolith. Biological and volcanic activity are locally significant at eastern Taylor Valley and in the summit area of Erebus Volcano, respectively. The salts have accumulated over the lifetime of the region, that is over less than the last 20-25 Ma or so. There is no evidence that they are relics from earlier, preglacial times, except for very minor amounts of gypsum and calcium carbonate. There has been a recent influx of sea water into Taylor Valley perhaps between 50,000 and 20,000 years ago, and evaporation of this water has preceded advance of Taylor Glacier over part of the resulting salt deposit. The continuing interaction between glacier and salt is causing basal ice to melt and producing aperiodic discharges of up to a few thousand cubic metres of salty water from the terminus of the glacier.